The Strategy Gap - Michael Coveney Michael Coveney Michael Coveney Michael Coveney Michael Coveney, Dennis Ganster (John Wiley & Sons, Inc., 2003)
We often come across companies that have set an ambitious longterm goal, perhaps to double revenue and profits over five years, or to dramatically increase the proportion of revenues coming from new businesses, but have devoted almost no intellectual effort to thinking through the medium-term capability-building program that is needed to support that goal. In too many companies there is a grand, and overly vague, long-term goal on one hand . . . and detailed short-term budgets and annual plans on the other hand . . . with nothing in between to link the two together. . . . There seems to be, in many companies, an implicit assumption that the short term and long term abut each other, rather than being dovetailed together. But the long term doesn’t start at year five of the current strategic plan. It starts right now!1